Pengembangan pembelajaran penemuan terbimbing untuk meningkatkan berpikir kritis dan motivasi belajar geometri di SMP - Siti Nuriyatin; Hartono Hartono (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2016)
Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran berbasis penemuan terbimbing untuk meningkatkan kemampuan berpikir kritis dan motivasi belajar matematika pada bangun ruang di SMP. Perangkat yang dikembangkan meliputi silabus, 3 RPP, 8 handout, 8 LKS, 1 perangkat tes ketercapain pada bangun ruang sisi datar; serta silabus, 3 RPP, 2 handout, 4 LKS, 1 perangkat tes ketercapaian kompetensi pada bangun ruang sisi lengkung. Penelitian ini adalah penelitian pengembangan (research development) dengan menggunakan model pengembangan 4D yaitu define, design, development, dan disseminate. Kevalidan perangkat ditinjau dari penilaian para ahli, kepraktisan ditinjau dari penilaian guru, penilaian peserta didik, dan observasi keterlaksanaan pembelajaran. Keefektifan ditinjau dari tes ketercapaian kompetensi, tes kemampuan berpikir kritis, dan motivasi belajar matematika peserta didik. Hasil penelitian menunjukkan bahwa perangkat pembelajaran yang dikembangkan valid, praktis, dan efektif.Kata kunci: pengembangan, perangkat pembelajaran, penemuan terbimbing, berpikir kritis, motivasi belajar matematika Developing of guided inquiry-based learning to increase critical thinking and motivation to learn on geometry in junior high school AbstractThis research is aimed to describe the development phase of guided inquiry-based learning package to increase critical thinking ablity and motivation to learn mathematics on solid figures and describe the quality of the developed product. The learning package consist of syllabus, 3 lesson plans, 8 handouts, 8 student work sheets, a competency achievement test on plane solid figure; and syllabus, 3 lesson plans, 2 handouts, 4 student work sheets, a competency achievement test on curve solid figure. This research is a developmental research study. The model of the instructional package in this research was adapted from 4-D development model. It consisted of five phases: define, design, develop, dan disseminate. The result of validation by expert jugdement shows that the kit that is developed is of valid category for each learning kit that has been developed. The aspects of practicality was of very practice category as seen from the evaluation by the teachers, evaluation by the students, and implementation of the learning. The aspect of effectiveness could be reached from the competency achievement test results, critical thinking ability test results, and the results of questionnaires of student’s motivation to learn mathematics. The result of this research is an instructional package component on solid figures is valid, practical, and effective.Keywords: development, instructional package, guided inquiry, critical thinking, motivation to learn mathematics